Decentralized Blockchain-Based Traceability Systems in Agricultural Supply Chains: A Global Perspective on Data Security, Transparency, and Equity - Aristarkus (CV. HEI PUBLISHING INDONESIA, 2024)
Decentralized blockchain-based traceability systems offer a solution to challenges in global agricultural supply chains, including lack of transparency, data security, and equity. This study investigates how blockchain, integrated with IoT, enhances data integrity, automates validation, and ensures fair benefit distribution from farm to consumer. Using a mixed-methods approach, including prototype development on Ethereum and Hyperledger, the research evaluates system efficiency, security, and socio-economic impacts. Results show significant improvements in data transparency, trust, and reduced tampering risks, empowering smallholder farmers. While private blockchains excel in efficiency, balancing transparency with data privacy and addressing infrastructure remain challenges. The study concludes that these systems hold substantial potential for creating more secure, transparent, and just agricultural supply chains globally.